SINGLE AND MULTIPLE ISCHEMIC BRAIN MICROLESIONS AFTER CAROTID ARTERY STENTING - E. S. Bulgakova; T. V. Tvorogova; В. A. Rudenko; O. М. Drapkina (Рациональная фармакотерапия в кардиологии)
Aim. To identify most probable cardiovascular predictors of periprocedural ischemic brain microlesions after carotid artery stenting (CAS) accounting its presumable pathogenesis.Material and methods. 84 patients with carotid artery stenosis undergoing CAS in a specialized medical center were examined. Diffusion-weighted imaging (DWI) magnetic resonance imaging was performed in all patients before and after intervention.Results. Among selected patients aged 40 to 83 years (mean age of 60.6Ѓ}3.9 years, male 80.95%) 39 (46.4%) patients had new ischemic brain microlesions after CAS, differently located. Among all patients (n=84) microlesion count correlated with age (γ=0.243; p<0.01), preprocedural hemoglobin level (γ=-0.278; p<0.01), systolic blood pressure (SBP) level before CAS (γ=0.190; p<0.05) and diastolic blood pressure (DBP) level 1 hour after CAS (γ=-0.201; p<0.05). In patients with microlesions their count (n=39) correlated with SBP and DBP levels 15 min after CAS (γ=-0.370; p<0.01 and γ=-0.369; p<0.01, respectively), percentage of SBP and DBP levels decrease during CAS (γ=0.404; p<0.01 and γ=0.458; p<0.001, respectively), SBP level 24 h after CAS (γ=-0.272; p<0.05) and body mass index (γ=-0.260; p<0.05). Patients with multiple microlesions (n=25) differed from patients without lesions (n=45) older age (67.0 [64.0; 77.0] vs 64.0 [60.0; 70.0], p<0.05), lower preprocedural hemoglobin level (130.9Ѓ}14.5 vs 139.5Ѓ}13.6, p<0.01), lower percentage of smokers (32.0% vs 57.8%, p<0.05), previous ipsilateral stroke (36.0% vs 13.3%, p<0.05) and persistent periprocedural arterial hypotension (12.0% vs 2.2%, p<0.05). These patients with multiple microlesions had more significant DBP level decrease (17.0 [10.0; 25.0] vs 6.5 [1.3; 11.8], p<0.05) compared with patients with single lesions (n=14). In the group of patients with single brain microlesion, unstable (71.4% vs 40.0%, p<0.05) and calcified (64.3% vs 28.0%, p<0.05) atherosclerotic plaques were seen more often compared with patients with multiple lesions. Patients with single brain microlesion differed from patients without lesions greater frequency of calcified atherosclerotic plaques (64.3% vs 31.1%, p<0.05), usage of proximal embolic protection devices (21.4% vs 0.0% p<0.01) and predilatation (35.7% vs 13.3%, p<0.05), perioperative neurological symptoms (21.4% vs 4.4%, p<0.05, and higher SBP levels during 24 h after CAS (mean values 137-122 mm Hg vs 120-112 mm Hg, p<0.05).Conclusion. Single microlesion is associated with unstable or calcified plaques and CAS technical complexities. Multiple microlesions may be associated with periprocedural hemodynamic instability and cerebral hypoperfusion risk factors.